2020
DOI: 10.1186/s12879-020-4904-4
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the FilmArray ME panel in laboratory routine using a simple sample selection strategy for diagnosis of meningitis and encephalitis

Abstract: Background: Infectious meningitis is a serious disease and patient outcome relies on fast and reliable diagnostics. A syndromic panel testing approach like the FilmArray ME can accelerate diagnosis and therefore decrease the time to pathogen specific therapy. Yet, its clinical utility is controversial, mainly because of a remaining uncertainty in correct interpretation of results, limited data on its performance on clinical specimens and its relatively high costs. The aim of this study was to analyze clinical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 52 publications
1
10
1
Order By: Relevance
“…Our results join those in a growing literature positioning the syndromic assay more as a screening test and not replacing conventional assays and recommending that it never be used as a “standalone” diagnostic option, especially in the presence of severe clinical presentations ( 2 , 6 , 9 ). We agree with the postulate that such a “simple” technique requires experienced users for accurate interpretation and discernment to properly interpret false-negative and false-positive results ( 6 , 11 ). Further studies are warranted concerning feedback on the use and potential adaptation of this algorithm, which we first plan to apply to pediatric patients in our hospital to optimize the utilization of both syndromic and specific assays.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results join those in a growing literature positioning the syndromic assay more as a screening test and not replacing conventional assays and recommending that it never be used as a “standalone” diagnostic option, especially in the presence of severe clinical presentations ( 2 , 6 , 9 ). We agree with the postulate that such a “simple” technique requires experienced users for accurate interpretation and discernment to properly interpret false-negative and false-positive results ( 6 , 11 ). Further studies are warranted concerning feedback on the use and potential adaptation of this algorithm, which we first plan to apply to pediatric patients in our hospital to optimize the utilization of both syndromic and specific assays.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, we mainly observed false-negative results in cases of the pathogen not being included in the panel of sought targets, highlighting the remaining position of bacterial culture as a gold standard. In cases of positive diagnosis, bacterial culture is obviously still necessary for antimicrobial susceptibility testing ( 11 ). The main issue for bacterial targets is still the low but significant rate of false-positive FilmArray results.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that a preselection for CSF cell count and clinical presentation needs to be taken into consideration before the is used. Studies with such a pre-selection (e.g., positive gram stain, detection of leukocytes and/ or bacteria, urgent clinical suspicion) show relatively high detection rates of pathogens in comparison to other studies [20]. Use of the array in patients with no suspicion for a CNS infection or in samples with normal CSF cell count could be avoided [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the FilmArray ME Panel should not be used as the only microbiological test and must be complemented by other techniques. 6 Metagenomic Next-Generation Sequencing for Diagnosis of Meningitis Metagenomic next-generation sequencing is an unbiased, hypothesis-free method of assessing for any microbial genetic material in the CSF. 7 Using this technique, a 2019 study of 204 pediatric and adult patients with meningitis or encephalitis identified 13 infections not discovered through other testing modalities; 7 of these 13 diagnoses guided change in treatment.…”
Section: Polymerase Chain Reaction-based Assaysmentioning
confidence: 99%
“…Finally, even when diagnostic testing is accurate, antimicrobial susceptibility testing requires concurrent use of standard culture techniques. Therefore, the FilmArray ME Panel should not be used as the only microbiological test and must be complemented by other techniques 6 …”
Section: Microbiological Diagnosismentioning
confidence: 99%